Hygrothermal performance of vernacular stone in a desert climate. (20th August 2019) - Makhlouf, Nahla N.; Maskell, Daniel; Marsh, Alastair; Natarajan, Sukumar; Dabaieh, Marwa; Afify, Mohamed Moemen
Highlights: Hygrothermal performance of Karshif stone investigated for the first time. Karshif had the superior moisture buffering value of 3.48 g/m 2 RH%. Results from standard testing conditions do not reflect in-situ performance. Testing conditions should instead be representative of service conditions. Abstract: Remote desert communities are often the most vulnerable to temperature extremes, as lack of access to reliable electricity prevents the use of active cooling or heating. Hence, there is a need to investigate how the building envelope itself can be used to passively regulate indoor environments. Readily available vernacular building materials in such areas are thought to aid in not only attenuating temperature swings but also moisture regulation, which improves comfort in a dry climate. Thus, the aim of this research is to investigate the hygrothermal properties of three different stone types commonly used as building materials in the Western Desert of Egypt: sandstone, limestone and, uniquely, Karshif, a rock rich in sodium chloride. The materials' thermal conductivity, moisture sorption and buffering, water vapour resistance, porosity distribution and phase composition are experimentally investigated. Our results show that the local perception of limestone buildings having poor indoor comfort, despite the material's superior thermal conductivity and specific heat capacity is only explainable through the relative superiority of sandstone and Karshif in moisture buffering. Vernacular materials need to be tested in environmental conditions representative of their local climate, rather than standardised conditions, as the latter may paint an incorrect picture of performance which, in the case of Karshif, led to partial dissolution under relative humidity of greater than 80%. However, testing under typical desert conditions demonstrates that both Karshif and sandstone are viable building materials that exhibit excellent moisture regulation behaviour. Since building materials in desert conditions may have to withstand atypical weather extremes, including rain, local materials need to be utilised within carefully designed wall assemblies or treated wall sections and, in the case of Karshif, not used in areas where relative humidity regularly reaches 80%. These findings are an important contribution in validating the performance of vernacular stone, and more widely, in demonstrating the importance of selecting appropriate testing conditions.